Reliability and validity of the Chinese version of the Family Resilience Questionnaire (FaRE Questionnaire) in patients with breast cancer: a cross-sectional study. Issue 4 (20th April 2022) - Li, Mengmeng; Ma, Rui; Zhang, Shanfeng; Wang, Shanshan; Jiao, Jiawei; Liu, Lamei; Wang, Panpan; Zhang, Zhenxiang; Wang, Peng; Li, Xiaoyan
Abstract : Objective: The aim of this study was to assess the reliability and validity of the Chinese version of the Family Resilience (FaRE) Questionnaire among patients with breast cancer in China. Design: It was a cross-sectional study, which involved translation, back-translation, cultural adjustment and psychometric testing of a 24-item FaRE Questionnaire. Setting: Three tertiary hospitals in Zhengzhou, China: respectively are the First Affiliated Hospital of Zhengzhou University, Second Hospital Affiliated to Zhengzhou University and Henan Provincial People's hospital. Participants: A total of 559 patients with breast cancer volunteered to participate in the study Primary outcome measures: Data analysis was performed using the IBM SPSS software V.21.0 and AMOS software V.21.0. Cronbach's α coefficient was used to examine the internal consistency. The test–retest reliability was calculated using the intraclass correlation coefficient on 30 participants. The content validity index was calculated based on the values obtained from six expert opinions. Construct validity test was performed using factor analysis including exploratory factor analysis and confirmatory factor analysis. Results: For the Chinese version of FaRE Questionnaire, the Cronbach's α coefficient of the total questionnaire was 0.909, and Cronbach's α coefficients of four factors were 0.902, 0.932, 0.905 and 0.963, respectively. The test–retest reliability index of the total questionnaire was 0.905. The Scale-Content Validity Index was 0.97, and Item-Content Validity Index ranged from 0.83 to 1.00. The questionnaire included 24 items, exploratory factor analysis extracted four factors with loading >0.4, which could explain 72.146% of the total variance. Confirmatory factor analysis showed the Chinese version of FaRE Questionnaire had an excellent four-factor model consistent with the original questionnaire. Conclusion: The Chinese version of FaRE Questionnaire has acceptable reliability and validity among patients with breast cancer in China. It can effectively assess family resilience and provide basis for personalised family resilience interventions for patients with breast cancer.